Penerapan Model Pembelajaran Tematik pada Mata Pelajaran IPS Siswa Kelas III SD Inpres Unggulan Toddopuli Makassar - Abdul Wahid; Nur Afni (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
Implementation of thematic learning models on the application of teaching methods and learning facilities in social studies subjects. The results of the study revealed that to understand the facts of the process starting from planning, it turned out that all teachers used lesson plans well in accordance with procedural standards and content standards. Determining the theme in determining the teacher's theme has met good standards because the selected theme is adjusted to the characteristics of students, interests, the environment and the local area in thematic learning. The implementation of the teacher has carried out the initial, core, and final activities that are effective and efficient and the assessment in the teacher's assessment has carried out according to what was made in the RPP well. Assessment tools used by teachers can be in the form of tests and non-tests. To understand the teacher's level of understanding in using the lecture method, discussion method, question and answer method, demonstration method, it turns out that in the application of the method it has been used well in accordance with the material being taught on the application of thematic learning models in social studies subjects.